Development of a customized three-dimensional bolus using transparent gel wax and its application in electron beam therapy - Young Jin Won; Jung Ju Jo; Su Ah Yu; Su Jung Shim; Kum Bae Kim; Jung Hoon Kim; Sang Hyoun Choi; Samju Cho (Physical and Engineering Sciences in Medicine, 2026)
Abstract This study aimed to develop a customized bolus using commercially available transparent gel wax (TGW) without requiring 3D printing technology and to evaluate its applicability in radiotherapy, including its physical and dosimetric characteristics. A dental alginate impression was taken from the curved surface of a mastectomy phantom to replicate the patient’s skin contour. Based on this, a silicone mould was fabricated, into which TGW was poured to form the customized bolus. The fabricated bolus was evaluated for its physical properties (density, electron density, homogeneity) and bolus conformity index (BCI), treatment planning dosimetric analysis, and actual dose measurements using optically stimulated luminescent (OSL) dosimeters, in comparison with a conventional vinyl gel sheet bolus (SuperFlex). The TGW bolus demonstrated high transparency and excellent homogeneity (standard deviation of internal HU: ±5.1), and its BCI was 0.03, indicating a very high level of conformity to the virtual bolus. Under 6 MeV and 8 MeV electron beam conditions, the TGW bolus showed mean dose errors of − 0.2% ± 1.3% and 0.5% ± 1.2%, respectively, which were numerically comparable to those of the SuperFlex bolus (0.6% ± 1.8% and − 2.1% ± 1.4%, respectively), with both systems providing clinically acceptable dose accuracy. In particular, the TGW bolus showed superior conformity and reproducibility in regions with high surface curvature, effectively reducing dose loss caused by air gaps. TGW is a low-cost, transparent, and flexible material that enables rapid fabrication (within one day) of a customized bolus through a simple moulding process. Its superior physical stability and equivalent dosimetric performance compared to existing products suggest strong potential for clinical application in radiotherapy.